h - Chiu, Dickson K. W.; Bellatreche, Ladjel; Sasaki, Hideyasu; Leung, Ho-fung.; Cheung, Shing-Chi.; Hu, Haiyang; Shao, Jie.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book contains the carefully selected and reviewed papers presented at three satellite events that were held in conjunction with the 11th International Conference on Web Information Systems Engineering, WISE 2010, in Hong Kong, China, in December 2010. The collection comprises a total of 40 contributions that originate from the First International Symposium on Web Intelligent Systems and Services (WISS 2010), from the First International Workshop on Cloud Information Systems Engineering (CISE 2010) and from the Second International Workshop on Mobile Business Collaboration (MBC 2010). The papers address a wide range of hot topics and are organized in topical sections on: decision and e-markets; rules and XML; web service intelligence; semantics and services; analyzing web resources; engineering web systems; intelligent web applications; web communities and personalization; cloud information system engineering; mobile business collaboration.
Keywords: Computer science; Computer Communication Networks; Information systems; Database management; Artificial intelligence; Computer vision; Computer Science; Information Systems Applications (incl. Internet).; Information Systems and Communication Service; Computer Communication Networks; Database Management; Artificial Intelligence (incl. Robotics).; Computer Imaging, Vision, Pattern Recognition and Graphics